Formation of critical citizenships as a tool against the proliferation of antidemocratic discourses: the importance of moving from concepts to experience in the Chilean and Costa Rican educational systems - Jara Pérez, Katherine Pamela (2024)
We find ourselves in an international political scenario marked by tensions: new armed conflicts and others that seem to refuse to disappear, political discourses that relativize the most elementary principles of democracy and human rights. This is a situation from which Latin America has not been exempt, on the contrary; our time is witnessing the proliferation of populist and authoritarian movements. Faced with this panorama, the following essay vindicates critical pedagogy as a basis for the development of critical and disruptive citizenship in school environments in relation to the hegemonic project expressed in the official curricula. Thus, from the reflections generated by the teaching exercise in Chile and Costa Rica, the analysis of official documents and the theoretical baggage inherited from critical thinking, the need to position citizenship as a practical exercise is raised, which allows moving from conceptual approaches to other experiential ones; where the democratization of the word, deliberation, the defense of human rights and nature are tools that allow sketching truly equitable societies, respectful and capable of valuing the existing epistemic heritages in the different educational communities. All this in response to the increase of structural violence and proliferation-materialization of anti-democratic discourses that permeate the whole of Latin American societies.